Interventions for improving mental health in athletes: a scoping review - Ekelund, R.; Holmström, S.; Gustafsson, H.; Ivarsson, A.; Lundqvist, C.; Stenling, A. (International Review of Sport and Exercise Psychology, 2025)
The aims of this scoping review were to map the current literature on interventions for improving mental health in athletes, identify knowledge gaps, and generate future research questions. The Preferred Reporting Items for Systematic Review and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guided this review. A systematic literature search was conducted in SPORTDiscus, PsycINFO, and SCOPUS and 44 intervention studies met the inclusion criteria. Results showed that 22 studies (50%) implemented cognitive behavioural principles, and the majority of these studies were influenced by various mindfulness programmes. Most studies (93%) included healthy athlete samples, and athletes aged 15-19 were the most examined age group (43%). Only three studies used clinical criteria in their sampling of participants and mediators were examined in two studies. The scarcity of studies examining mediators and subclinical or clinical samples revealed critical knowledge gaps in the literature. Furthermore, the critical appraisal showed that regardless of study design, most studies demonstrated low internal validity. We propose the use of high-quality single-case studies with athletes who experience subclinical or clinical mental health issues, and further investigation of mechanisms of change linking intervention components to outcomes of interest.